1964
DOI: 10.1139/v64-240
|View full text |Cite
|
Sign up to set email alerts
|

C13 CHEMICAL SHIFTS IN ORGANIC CARBONYL GROUPS

Abstract: The results of a study of the resonance position of the carbonyl carbon nucleus in an extensive series of carbonyl derivatives are reported. A discussion of the major factors affecting the position of these carbon resonances is presented and some of the potential applications of these data to chemical problems are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
2

Year Published

1965
1965
1985
1985

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(47 citation statements)
references
References 6 publications
3
41
1
2
Order By: Relevance
“…All of the data in Tables 11-V were obtained using the neat liquids, but to examine the effect of hydrogen bonding a t the carbonyl oxygen on the shieldings of these nuclei some compounds were examined in methanol solution as well (Table VII). (1). Certain consistent trends can be seen for the effects of further alkyl substitution on the alp-unsaturated carbonyl system by comparing the rest of the data.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…All of the data in Tables 11-V were obtained using the neat liquids, but to examine the effect of hydrogen bonding a t the carbonyl oxygen on the shieldings of these nuclei some compounds were examined in methanol solution as well (Table VII). (1). Certain consistent trends can be seen for the effects of further alkyl substitution on the alp-unsaturated carbonyl system by comparing the rest of the data.…”
Section: Introductionmentioning
confidence: 54%
“…While the overall consistency of the effects of inethyl substitution tends t o support the present assignments, a potential method of confirming our conclusions seemed worth investigating. I t has been established that hydrogen-bonding solvents tend to reduce the shielding of carbonyl carbon nuclei relative t o that measured for the pure liquid or in nonpolar solvents (1,4,5,35). This reduction, although not particularly large unless protonation occurs (35), is significant and, furthermore, in aromatic systenls the effect appears t o be reflected a t the terminal carbon nucleus as well [i.e., C-4 in acetophenone (I)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation indicates that in the preferred conformation of ceramide and glucosylceramide the steric hindrance between the allylic hydroxy group and the olefinic proton H-4 or between the allylic hydroxy group and the carbonyl oxygen is greater in the threo than in the erythro configuration. In addition, the downfield shift observed for the resonance of the carbonyl carbon of threo-ceramide and glucosyl-threo-ceramide suggests an intramolecular hydrogen bonding between the carbonyl oxygen and the hydroxyl group [19]. This hydrogen bonding should lessen the polarity of these threo compounds with respect to the erythro compounds.…”
Section: Discussionmentioning
confidence: 94%
“…for the same change in substituent. An interpretation of the 13C results was advanced (1) in terms of the resonance forms contributing to the structures of these compounds in which it was suggested that the location of a nucleus within the aryl system could be an important factor governing substituent effects on its shielding. In the fluorobenzenes the fluorine nucleus is at the end of the resonance system while the carbonyl carbon in the aryl ketones is one atom from the end.…”
Section: Introductionmentioning
confidence: 99%